Pengembangan sistem informasi pembayaran SPP berbasis web yang didukung dengan notifikasi whatsapp - Hesty Kumala Sani; Ambiyar Ambiyar; Sukardi Sukardi; Delima Yanti Sari (Universitas Negeri Padang, 2022)
The use of the internet at the Cersa Pasaman Vocational High School (SMK) is still not optimal, the internet is only used for school information and there is no school financial information system. Based on observations, tuition payments at schools are still manual and make the work of the finance department slower. This type of research is research and development data retrieval is carried out to users of the web-based SPP payment information system. The research sample consisted of 30 people consisting of 5 people for a limited trial and 25 people for a wider trial taken from the principal, Administration Officer, teachers and students of SMK Cersa Pasaman, the instrument of this research was a questionnaire to determine the feasibility of the SPP payment information system. The results obtained from this research development is a web-based tuition payment information system. Based on the results of this study, it can be concluded that the developed information system is declared valid with an average value of 85.67%. The information system developed was very practical from the results of the limited trial to teachers and students with an average value of 92.60%, while the results of a wider trial obtained an average value of 92.68%. Based on the findings of this study, it was concluded that the web-based SPP payment information system at SMK Cersa Pasaman was valid, practical and feasible to use for student tuition payments.